The Italian School of Public Finance at the Turn of the Twentieth Century and the Ricardian Equivalence Theorem - Stefano Toso (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1991)
In this paper we re-examine the contribution of the Italian tradition of public finance to the issue of differential incidence of tax and debt financing. The protracted controversy, now restated as whether government bonds are considered as net wealth, goes back to Ricardo's proposition that the method of financing any particular level of government expenditure is irrelevant. As a matter of fact, it is only at the turn of this century that we get a critical evaluation of that proposition and its assumptions, which remained implicit in Ricardo's work. This was accomplished by the Italian school of public finance. That remarkable contribution has largerly been neglected by the subsequent Anglo-Saxon literature and even the current views seem to be essentially anticipated by those earlier studies.
Keywords: 330